Reclamação Constitucional - Abreu, Vinícius Caldas da Gama e (2019)
The primary concern of this study is to present a theoretical analysis of the constitutional complaint and to demonstrate how its use in Brazilian Courts is being carried out, especially after the advent of the Civil Procedure Code in 2015. Since its historical creation by Supreme Court jurisprudence, grounded on the doctrine of implied powers, the constitutional complaint underwent considerable evolution, and received constitutional status by the original constituent power of 1988 and legislative enlargement by the Civil Procedure Code in 2015, which consolidated it as an instrument of frequent use for the defense of the Court’s decision-making authority and of its competence. On that subject, this research will explore the legal nature of the complaint, proving it is a constitutional action, and will deal with each case of use of the constitutional complaint brought by the Constitution of 1988 and by article 988 of the Civil Procedure Code, relevant procedural issues, such as the structure and content of the initial petition, the legitimacy to act, the possibility of third party interventions, the possibility of granting interim injunctions, the structure and effects of the decision-making act and ways of reviewing the decision, in addition to issues that are subject of great controversy, such as the use of the constitutional complaint within State’s Small Claim Courts jurisdiction